The young hypertensive - B. Rayner (South African Family Practice)
Increasingly, hypertension in children and adolescents is becoming more prevalent as a result of the burgeoning obesity epidemic, and the effects of low birthweight and underlying genetic predisposition. Blood pressure (BP) is lower in children, and it is therefore imperative to consult age, gender, and height norms for BP. Pre-hypertension is defined as BP persistently above the 90th centile, and hypertension as BP persistently above the 95th centile. Before a diagnosis can be made, BP needs to be taken frequently, and 24-hour ambulatory BP monitoring is recommended. Contrary to expectation, most cases of elevated BP in adolescents are due to primary or essential hypertension. However, in each case, a full history and examination should be performed using a few basic investigations. Special investigations and referral need to be reserved for those children with a suspected secondary cause, and those with more severe hypertension. The mainstay of treatment is lifestyle modification, and pharmacotherapy should be reserved for patients with symptomatic or severe hypertension, secondary hypertension, hypertension with overt target-organ damage, type 1 and 2 diabetes, and persistent hypertension refractory to lifestyle intervention.